1983
DOI: 10.1029/jc088ic03p01563
|View full text |Cite
|
Sign up to set email alerts
|

Bathymetric prediction from SEASAT altimeter data

Abstract: The linear response function technique is used to analyze two 1300‐km tracks of SEASAT altimeter data and corresponding bathymetry in the Musician Seamounts region north of Hawaii. Bathymetry and geoid height are highly correlated in the 50‐ to 300‐km wavelength range. A predictive filter is developed which can operate on SEASAT altimetry in poorly surveyed oceanic regions to indicate the presence of major bathymétrie anomalies. Modeling of the bathymetry‐geoid correlation in the Musician region is attempted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(75 citation statements)
references
References 23 publications
1
70
0
Order By: Relevance
“…A major contribution to the marine geoid is made by seafloor bathymetry, because of the large density contrast at the rock-water interface. Attempts have therefore been made to use satellite altimeter data to predict bathymetry (e.g., Lazarewicz and Schwank, 1982;Dixon et al, 1983). Such a tool would be especially asd'ul in the South and West Pacific where ship crossings are rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major contribution to the marine geoid is made by seafloor bathymetry, because of the large density contrast at the rock-water interface. Attempts have therefore been made to use satellite altimeter data to predict bathymetry (e.g., Lazarewicz and Schwank, 1982;Dixon et al, 1983). Such a tool would be especially asd'ul in the South and West Pacific where ship crossings are rare.…”
Section: Introductionmentioning
confidence: 99%
“…(1984) showed that the Seasat radar altimetry and seafloor topography over Bermuda and Gregg Seamount could not be described adequately by a single transfer function. Dixon et al (1983) and Watts and Ribe (1984) related the variations in amplitude of marine geoid anomalies over seamounts to different effective elastic thicknesses of the flexed lithosphere beneath the seamounts. The effective elastic thicknesses are related to the tectonic settings of the seamounts, that is, whether they formed on or near a mid-oceanic ridge crest or off-ridge.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of complications that need careful handling; the most important ones are 1) computing bathymetry from gravity anomalies is possible over a limited wavelength band, and 2) longer wavelengths are highly dependent on the elastic thickness of the lithosphere. The feasibility study of a bathymetry calculation technique based on the one-dimensional filtering of SEASAT tracks is published elsewhere [9]. Fundamentally, the algorithm is based on the linear approximation of the relationship between the geoid and a given density contrast interface.…”
Section: Bathymetric Measurements Using Altimetrymentioning
confidence: 99%
“…Altimetry-derived bathymetry also reveals plate boundaries and oceanic plateaus. The basic theory for deducing seafloor topography from satellite altimeter measurements is summarized elsewhere [9]. The conceptual approach uses the sparse in situ depth soundings to restrict the long-wavelength depth while the shorter-wavelength topography is inferred from the downward-continued satellite gravity measurements [10] [47].…”
Section: Bathymetric Measurements Using Altimetrymentioning
confidence: 99%
See 1 more Smart Citation